A comprehensive overview of exosome lncRNAs: emerging biomarkers and potential therapeutics in endometriosis - Wang, Min; Zheng, Lianwen; Lin, Ruixin; Ma, Shuai; Li, Jiahui; Yang, Shuli (Frontiers in Endocrinology, 2023)
Endometriosis is a gynecological condition that significantly impacting women’s daily lives. In recent years, the incidence of endometriosis has been rising yearly and is now an essential contributor to female infertility. Exosomes are extracellular vesicles (EVs) that carry long noncoding RNA (lncRNA) and shield lncRNA from the outside environment thanks to their vesicle-like structure. The role of exosome-derived lncRNAs in endometriosis is also receiving more study as high-throughput sequencing technology develops. Several lncRNAs with variable expression may be crucial to the emergence and growth of endometriosis. The early diagnosis of endometriosis will be considerably improved by further high specificity and sensitivity Exosome lncRNA screening. Exosomes assist lncRNAs in carrying out their roles, offering a new target for creating endometriosis-specific medications. In order to serve as a reference for clinical research on the pathogenesis, diagnosis, and treatment options of endometriosis, this paper covers the role of exosome lncRNAs in endometriosis and related molecular mechanisms.